Indirect estimation of cable tension during gymnastic movements - Brewin, M. A.; Kerwin, D. G. (Sports Engineering, 2003)
Knowledge of external forces acting on an athlete is often required to study performance and injury mechanisms, but direct measurements are difficult to obtain. While transducers in the rings cables typically measure external forces experienced by gymnasts performing static balances and swinging movements on rings, this solution is not always acceptable and an accurate technique that does not hinder the gymnasts` performances is desirable. This study evaluates a video-based technique for estimating cable tension on the rings apparatus. Static loading of a rings frame coupled with a planar video analysis of the mandatory damped elastic devices (DEDs) provided a tension-deflection calibration curve. Three-dimensional video and cable tension data were obtained for two male gymnasts performing static balances and dynamic swinging movements. Cable tension was measured using a force link while a planar video analysis determined time histories of the DED deflections. Combined cable tension time histories were estimated fromrelative DED deflections coupled with the tension-deflection calibration curve and the orientation of the rings cables, and were compared to measured values to evaluate the proposed technique. For static balances the RMS difference between measured and estimated combined cable tension was 83 N. For dynamic swinging movements the maximum RMS difference was 189 N, equivalent to a 4% difference when expressed as a percentage of the peak value. The indirect video-based technique developed in this study accurately estimates combined cable tension throughout movements on rings and may be considered for studies where a remote measurement is required. There is potential for the technique to be extended to other sporting situations, where indirect accurate estimates of external forces acting on an athlete are needed.